2006
DOI: 10.1038/modpathol.3800566
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical investigation of tumorigenic pathways in small intestinal adenocarcinoma: a comparison with colorectal adenocarcinoma

Abstract: Small intestinal adenocarcinoma is an uncommon neoplasm morphologically similar to or indistinguishable from colorectal adenocarcinoma. Although much has been learned about genetic pathways critical to colorectal tumorigenesis, little is known about molecular alterations involved in the development of small intestinal adenocarcinoma. In this study, we immunohistochemically compared non-ampullary small intestinal adenocarcinomas with sporadic colorectal adenocarcinomas for the expression of several proteins kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 34 publications
5
36
0
2
Order By: Relevance
“…Colorectal cancer cases that are negative for CDX2 expression tend to be poorly differentiated tumours, and consistent with this finding, we observed that whereas 100% of well-differentiated tumours were % 70 57 31 43 15 28 13 Negative, % 30 43 69 57 85 72 CDX2 positive, only 58% of poorly differentiated tumours were CDX2 positive (Werling et al, 2003). The reported incidence of abnormalities in MMR genes in SBA patients has been variable, ranging from 5 to 45% by microsatellite testing and from 0 to 26% by immunohistochemical staining of tumour samples (Hibi et al, 1995;Rashid and Hamilton, 1997;Blaker et al, 2002;Planck et al, 2003;Brueckl et al, 2004;Zhang et al, 2006). In our study, we saw a higher rate of defective MMR, with 35% of patients showing loss of MMR protein expression.…”
Section: Discussionsupporting
confidence: 73%
“…Colorectal cancer cases that are negative for CDX2 expression tend to be poorly differentiated tumours, and consistent with this finding, we observed that whereas 100% of well-differentiated tumours were % 70 57 31 43 15 28 13 Negative, % 30 43 69 57 85 72 CDX2 positive, only 58% of poorly differentiated tumours were CDX2 positive (Werling et al, 2003). The reported incidence of abnormalities in MMR genes in SBA patients has been variable, ranging from 5 to 45% by microsatellite testing and from 0 to 26% by immunohistochemical staining of tumour samples (Hibi et al, 1995;Rashid and Hamilton, 1997;Blaker et al, 2002;Planck et al, 2003;Brueckl et al, 2004;Zhang et al, 2006). In our study, we saw a higher rate of defective MMR, with 35% of patients showing loss of MMR protein expression.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, at this time, final interpretation is not possible due to the absence of direct comparison using the same techniques between CD-associated SBA and sporadic SBA, the small size of our series, the fact that it is not possible to know if the tumors exhibiting b-catenin abnormalities in the previously published series are sporadic or CD-associated SBA. [55][56][57][58] In addition, the significance of isolated cytoplasmic b-catenin staining in the absence of nuclear expression, as a marker of b-catenin mutation, has been questioned. 56 Finally, as for i-CRC, we found high nuclear TP53 expression in the four CD-associated SBA tissue samples, a pattern suggesting that TP53 might be an actor of small intestinal carcinogenesis in CD patients, presumably as a result of chronic inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…[55][56][57][58] In addition, the significance of isolated cytoplasmic b-catenin staining in the absence of nuclear expression, as a marker of b-catenin mutation, has been questioned. 56 Finally, as for i-CRC, we found high nuclear TP53 expression in the four CD-associated SBA tissue samples, a pattern suggesting that TP53 might be an actor of small intestinal carcinogenesis in CD patients, presumably as a result of chronic inflammation. Previous studies, mostly performed on sporadic SBA mucosal samples, showed variable TP53 expression, ranging from 24%-51.8%.…”
Section: Discussionmentioning
confidence: 98%
“…57 Immunohistochemically, small intestinal adenocarcinomas more frequently express CK7, and less frequently express CK20, CDX2, and a-methylacyl coenzyme-A racemase, in comparison with CRCs. [58][59][60][61][62] Interestingly, a CK7 þ /CK20 À pattern is much more commonly seen in Crohn-associated small intestinal adenocarcinomas than in sporadic cases.…”
Section: Distinction Between Crc and Adenocarcinoma Of The Small Intementioning
confidence: 99%